FEATURES OF SNOW AND MOISTURE DISTRIBUTION UNDER THE INFLUENCE OF SHELTER BELTS OF DENSE CONSTRUCTION - Sidorenko, S. V.; Bila, Yu. M. (Forestry and Forest Melioration, 2018)
Introduction Field protective shelterbelts improve microclimate of agricultural land. Forest shelterbelts have a significant impact on the deposition and distribution of snow in the fields, freezing of the soil, its hydrophysical and chemical properties. Row shelterbelts minimize loss of productive land. Such plantations have a high snow-retaining capability. The forest strips allow most uniformly snow cover distribution in the fields, which contributes to the additional moisture of the soil, particularly in steppe and forest-steppe zones. The aim of the study was to determine the peculiarities of snow and moisture distribution under the influence of forest protective shelterbelts. Materials and Methods The study of the influence of different vertical density of shelterbelts on snow accumulation and soil moisture was conducted at various distances from forest belts in the research farm “Experimental field” of Kharkiv National Agrarian University named by V. V. Dokuchaev. A comparative estimation of ameliorative influence had been carried out on two typical experimental plots. We measured snow depth at different distances from the belts and determined the density and water equivalent of the snow cover using the method of forest meteorological observations and snow survey. Soil moisture was estimated during the period of active moisture exchange in the forest belts and in the control section (open field). Results The health condition of the forest belt No 31 was evaluated as “severely weakened”. It was found that the proportion of dead trees was 8 % in the middle row of the forest belt. In margin rows, it was 5 %. The health condition of the forest shelterbelt No 32 was estimated as “weakened”. The shelterbelt No 32 had better health, the proportion of dead trees in the forest rows ranged from 2 to 4 %. The death of individual trees in the belts provoked the appearance of natural renewal and, as a result, the structure of the examined forest belts had changed. During the study, their construction was classified as “dense”. As a result of the influence of the shelterbelt, the maximum water content in leeward snow trail was 47 % higher than the moisture reserves accumulated during the winter period in the open field (control plot). The results obtained from a regression analysis indicated that the distribution of snow cover on the experimental plot was determined by the distance from the shelterbelt by 90–95 % (R? = 0.95 and R? = 0.90). It was found that the soil moisture within the forest belt was much lower than at a certain distance from the belt (by 11–31 %). It may be explained by the active use of moisture by plants within the forest belt, which intensively transpired, while in the inter-boundary space, the agricultural plants only just began to grow at the moment of the study. It was found that the soil moisture increases with the distance from the belt with two peaks of the greatest humidity localization: at a distance of 30 m (approximately corresponds to the double height of the shelterbelt, where the largest amount of snow was accumulated) and in the middle of the field (micro lowland was detected in the center of the field). The changes in the soil moisture, depending on the distance to the belt (Ff = 18.6; Ft = 5.8; p = 0.01) and the sampling depth (Ff = 17.3; Ft = 5.8; p = 0.01), were statistically significant. Conclusions The death of a significant number of trees in the studied forest shelter belts led to undergrowth emerging and a change in the belt construction design from sparse (more productive) to dense (least productive). The maximum water equivalent of snow cover in snow trail in the leeward side of the forest belt was 47 % larger than water equivalent accumulated in the open field. Intensive use of soil moisture by plants within the protective forest belts significantly influenced the redistribution of moisture deep into the soil profile. 6 Figs., 5 Tables, 13 Refs.